Identification of quantitative trait loci for delta 13c and productivity in irrigated lowland rice - Laza, Ma. R.; Kondo, M.; Ideta, O.; Barlaan, E.; Imbe, T. (Wiley, 2006)
Stable carbon isotope ratio (δ13C) in plants has been suggested as a useful indicator for cumulative Ci/Ca signature in a leaf, water use efficiency, and crop productivity, and is known to have genotypic variation in rice (Oryza sativa L.). We conducted a field study to identify quantitative trait loci (QTLs) for δ13C and other related leaf traits, such as leaf N, specific leaf area, and SPAD value, using recombinant inbred lines derived from an indica × japonica cross grown under flooded conditions. We also examined the genetic associations of δ13C with yield, yield components, and biomass productivity. Putative QTLs for δ13C were identified on chromosomes 2, 4, 8, 9, 11, and 12 across plant parts, stages, and years. Differential expression of QTL for δ13C among stages suggests that each QTL had different functions by stages. The QTLs for δ13C were associated with a few colocated QTLs for leaf traits indicating that their physiological and genetic associations with leaf traits may be complex. Values of δ13C at maturity were negatively correlated with harvest index and grain yield. However, genetic association of these traits could not be clarified due to the absence of co‐located QTLs. Further examination would be useful to elucidate the physiological and morphological functions of QTLs for δ13C found in this study.